La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Au-delà des "vagues" #moiaussi : Cinq ans de mobilisation féministe en musique au Québec (2017-2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2022)

Interroger l'expérience d'un chœur féministe : le cas du Chœur Maha - Harrison-Boisvert, Catherine (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Quadruple défi pour les artistes femmes, immigrantes et allophones : Le cas du premier Sarau das Minas Montréal - Vasconcellos de Carvalho, Dalila (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Serving Each Other: Sharing Economies and Affective Labour in Montréal's Kiki Scene - Tailor, Jesse (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

Feminism, Media Technologies, and Studio XX: An Interview with Kim Sawchuk - Sawchuk, Kim; Tripp, Stephanie (Media-N: Journal of the New Media Caucus., 2013)
Kim Sawchuk is a feminist media studies scholar and a founding member of Studio XX, a feminist-run new media arts collective based in Montreal. A professor in the Department of Communication Studies at Concordia University, she is the former editor of the Canadian Journal of Communication and co-editor of wi: journal of mobile media. Sawchuk’s work encompasses the roles of women in science and technology, as well as issues surrounding media technology access and use by women, elders, and immigrant communities. Her more recent research involves the use of mobile devices by older adults. During a Skype interview with guest editor Stephanie Tripp on March 22, 2013, Sawchuk discussed her collaboration in Studio XX, her research on women and technology, her work on mobile communications technologies, and her outlook on issues facing women working in new media today.

De la cuisine au studio - Lupien, Anna (Éditions du remue-ménage, 2012)
De la cuisine au studio explore les parcours de douze artistes issues de trois générations différentes : femmes signataires du manifeste Refus global en 1948, premières cinéastes qui ont œuvré à l’ONF dans les années 1970 et artistes médiatiques impliquées au Studio XX. À partir d’entrevues avec les artistes, Anna Lupien pose un regard sociologique sur l’expérience de créatrices qui ont investi l’art en tant qu’espace d’expression dans la sphère publique. De quelle façon ont-elles élaboré des stratégies créatives et par le fait même donné corps à des transformations sociales engendrées par le mouvement féministe, notamment en ce qui a trait à la conciliation travail-famille ? Comment ont-elles intégré des milieux artistiques qui ne leur étaient pas ouverts d’emblée ? Comment se sont-elles engagées pour le bien commun à travers leur parcours artistique ? Les histoires de ces artistes – Madeleine Arbour, Christine Brault, Mireille Dansereau, Dorothy Todd Hénaut, Stéphanie Lagueux, Bérengère Marin-Dubuard, Helena Martin Franco, Terre Nash, Anne-Claire Poirier, Françoise Riopelle, Bonnie Sherr Klein et Françoise Sullivan – témoignent des luttes inachevées du mouvement féministe et des brèches qu’elles ont pratiquées dans l’ordre des choses, suscitant des rencontres originales entre l’art et le politiqu

De la cuisine au studio : le rapport public/privé interrogé au fil des parcours d'artistes québécoises de trois générations - Lupien, Anna (Université du Québec à Montréal, 2011)

« Un studio à soi ». Entrevue avec Bérengère Marin Dubuard, du Studio XX - Parent, Sylvie (ETC, 2008)
Un article de la revue ETC, diffusée par la plateforme Érudit.
Publisher: Revue d'art contemporain ETC inc.

Considering Complexity in Canadian Civil Society: A Case Study of Studio XX - Gerlach, Neil; Hamilton, Sheryl (Revista Mexicana de Estudios Canadienses, 2002)

Virtually Civil: Studio XX, Feminist Voices, and Digital Technology in Canadian Civil Society - Gerlach, Neil; Hamilton, Sheryl N. (Civic Discourse and Cultural Politics in Canada, 2002)

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation m the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.